2012
DOI: 10.1017/s0954579411000630
|View full text |Cite
|
Sign up to set email alerts
|

Emotional availability, attachment, and intervention in center-based child care for infants and toddlers

Abstract: According to data from the 1997 NICHD Study of Child Care, center-based child care can have deleterious effects on children's social-emotional development. We hypothesized that training child care professionals to develop positive relationships with children in their care would improve the quality of center-based child care. Thirty-three professional caregiver-child pairs participated in the intervention group and 24 professional caregiver-child pairs were assigned to a care as usual comparison group. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 55 publications
1
59
0
Order By: Relevance
“…However, taking into account potential negative effects of cortisol elevations early in life, supporting mother’s non-intrusiveness and children’s responsiveness seems to be a promising approach in order to reduce potential elevations of cortisol in association with kindergarten entry and thus promoting early child development. Previous studies have shown that the EA of a dyad is relatively stable across time, but that it is sensitive to change through interventions supporting emotional available caregiver-child relationships at home as well as in professional caregiving settings (Biringen et al, 2010, 2012, 2014; Baker et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…However, taking into account potential negative effects of cortisol elevations early in life, supporting mother’s non-intrusiveness and children’s responsiveness seems to be a promising approach in order to reduce potential elevations of cortisol in association with kindergarten entry and thus promoting early child development. Previous studies have shown that the EA of a dyad is relatively stable across time, but that it is sensitive to change through interventions supporting emotional available caregiver-child relationships at home as well as in professional caregiving settings (Biringen et al, 2010, 2012, 2014; Baker et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Biringen et al (2012) implemented an intervention program that includes information about attachment, emotional availability and practice, using video feedback to increase attachment between 57 caregivers and 57 young infants and toddlers who VOL. 11 NO.…”
Section: Establishing the Need For The Programmentioning
confidence: 99%
“…Biringen et al. () used the AQS as an outcome measure in testing the efficacy of a training program aimed at encouraging the emotional availability of childcare professionals toward toddlers in their care. In this study, the intervention group showed improvements on the AQS from pre‐ to posttest, as compared to the control group.…”
Section: Assessment Tools Related To Attachmentmentioning
confidence: 99%